(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2022)
This article explores how in The Novel of My Life Heredia’s tragedy -that is forced exile- stems from a dynamics between colonialism and culture in Cuba. At the same time, this dynamics reveals the transatlantic concatenations between the imperial politics of Spain and the colonial character of nineteenth-century Cuba. Heredia’s tragedy, I argue, is depicted in Padura’s novel as a consequence of a socio-historical reality in which Heredia’s enlightened, or liberal, ideas about politics and independence where rather “misplaced ideas” in the Cuba of the 1820s. In other words, some of these European liberal ideas became “misplaced ideas” when they were displaced first to the Spanish context, and subsequently to the colonial context in Cuba. The incongruences between the political structures and culture of the Spanish dynastic state and enlightened European ideas reflected themselves on colonial Cuba.